Verbal abuse during pregnancy increases frequency of newborn hearing screening referral: The Japan Environment and Children's Study. (April 2019) - Komori, Kaori; Komori, Masahiro; Eitoku, Masamitsu; Joelle Muchanga, Sifa Marie; Ninomiya, Hitoshi; Kobayashi, Taisuke; Suganuma, Narufumi; ,
Abstract: Background: Verbal abuse during pregnancy has a greater impact than physical and sexual violence on the incidence of postnatal depression and maternal abuse behavior towards their children. In addition, exposure of children (aged 12 months to adolescence) to verbal abuse from their parents exerts an adverse impact to the children's auditory function. However, the effect of verbal abuse during pregnancy on fetal auditory function has not yet been thoroughly investigated. Objective: The objective of the study was to examine the relationship between intimate partner verbal abuse during pregnancy and newborn hearing screening (NHS) referral, which indicates immature or impaired auditory function. Participants and setting: The Japan Environment and Children's Study is an ongoing nationwide population-based birth-cohort study designed to determine environmental factors during and after pregnancy that affect the development, health, or wellbeing of children. Pregnant women living in 15 areas of Japan were recruited between January 2011 and March 2014. Methods: Multiple imputation for missing data was performed, followed by multiple logistic regression using 16 confounding variables. Results: Of 104, 102 records in the dataset, 79, 985 mother–infant pairs submitted complete data for questions related to verbal and physical abuse and the results of NHS. Of 79, 985 pregnant women, 10, 786 (13.5%) experienced verbal abuse and 978 (1.2%) experienced physical abuse. Of 79, 985 newborns, 787 (0.98%) received a NHS referral. Verbal abuse was significantly associated with NHS referral (adjusted odds ratio: 1.44; 95% confidence interval: 1.05–1.98). Conclusions: Verbal abuse should be avoided during pregnancy to preserve the newborn's auditory function.